(untitled) (Heritage, 2022)
The scientific research institution Andrić Institute in Višegrad was founded in 2013 and in the same year it started publishing. Over a period of eight years, the Andrić Institute has published 107 titles of monographic publications and launched three titles of journals. In this paper, we consider the publishing activities of the Andrić Institute with the aim of considering its contribution to the development of certain scientific fields, primarily history, literature and linguistics. At the same time, we present his previous publishing production to the professional, scientific and general public.